The Effect of Giving Red Dragon Fruit Juice on Hemoglobin Levels in Pregnant Women at BPM Fifi Yanti, Agam Regency (HEALTH CARE: JURNAL KESEHATAN, 2025)
Anemia during pregnancy is one of the complications during pregnancy that can pose a risk to the health of the mother and fetus. Data on anemia in West Sumatra in 2022 was 14.5% while in BPM Fifi Yanti it was 15.6%. An alternative approach to dealing with anemia during pregnancy is through the utilization of natural resources as a form of local wisdom and complementary therapy. Dragon fruit contains many nutrients needed by the mother's body to form red blood cells. Consumption of dragon fruit can increase hemoglobin levels by 1.82%. The purpose of the study was to analyze the effect of giving dragon fruit juice on increasing Hb levels in pregnant women at PMB Fifi Yanti, Agam Regency. The method used in this study was pre-experimental through a one-group design before and after the intervention. The sample in this study was 15 pregnant women in the third trimester who were taken by purposive sampling. Data analysis using the Wilcoxon test. Based on this study, it was found that there was an increase in Hb in pregnant women with an average of 0.65 gr / dL so that most mothers who experienced mild or moderate anemia experienced an increase in Hb to normal. It is hoped that health workers will develop the provision of dragon fruit juice combined with the provision of Fe tablets so that anemia in pregnant women can be prevented as quickly as possible.